RESOLVING CONFLICT POTENTIAL: THE PREVENTIVE ACTION ON THE SHIA COMMUNITY IN YOGYAKARTA - Riza Saputra; Irza Melly; Siti Noor Aini; Ahmad Khotim Muzakka (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2020)
Since the 11th years ago the existence of the Syi'ah community in Yogyakarta lived in harmony with other groups of religions and society, however, in 2013, the leaflet is put in several places that mention "Syi'ah is not Islam." This notion ultimately intrigued some people to know about the existence of Syi'ah in Yogyakarta. Moreover, conflict potential may also occur because of this notion. This article will focus on the defendable entity of the Syi'ah community in Yogyakarta. The purpose of this paper is to identify the conflict potential among the Syi'ah community in Yogyakarta and to observe the prevention of this community from the conflict potential. In this respect, we carried out field research, interview with Syi'ah adherents in Yogyakarta and hamlet official indicating conflict potential and the way of Syi'ah community interaction and prevention within the contentious notion of anti-Syi'ah. This research finds the following results: conflict prevention which has been done is structural and operational. Syi'ah actively socializes with the society, does the dialogue with MUI and people who disagree with their existence, and being open to the people who want to discuss and study religious studies from their community.